Kpna7 interacts with egg‐specific nuclear factors in the rainbow trout (Oncorhynchus mykiss). Issue 12 (15th December 2014) - Wang, Lei; Ma, Hao; Fu, Liyuan; Yao, Jianbo
SUMMARY Nuclear proteins are required for the initiation of transcription in early embryos before embryonic genome activation. The regulated transport of nuclear proteins is mediated by factors known as importins (karyopherins). Kpna7, a newly discovered member of the importin α family, is critical for early development in mammals. In this study, we characterize rainbow trout Kpna7. The cDNA for rainbow trout Kpna7 encodes a 519 amino acid protein that contains a conserved importin β binding (IBB) domain and seven armadillo/beta‐catenin‐like repeat (ARM) motifs. Reverse‐transcriptase PCR and Western blot analyses revealed that Kpna7 is specifically expressed in eggs/ovary. Real‐time PCR analysis demonstrated that expression of Kpna7 mRNA is high in unfertilized eggs, gradually decreases in early‐stage embryos until 3 days post‐fertilization, and declines sharply thereafter, reaching a level that is barely detectable in 4‐day‐old embryos. Using a yeast two‐hybrid screening system, we identified two Kpna7‐interacting proteins from a rainbow trout egg cDNA library: Stl3 (rhamnose‐binding lectin 3) and an uncharacterized protein. Both genes appear to be expressed specifically in eggs/testis. Co‐immunoprecipitation assays confirmed the interaction between Kpna7 and Stl3, and co‐transfection experiments using EGFP‐tagged Stl3 showed that Kpna7 facilitates the nuclear transport of Stl3 through an interaction with the predicted nuclear‐localization signal cluster at the carboxy‐terminus of Stl3. Our data suggest that Kpna7 may function in early embryonic development as a unique nuclear transporter for egg‐specific proteins. Mol. Reprod. Dev. 81: 1136–1145, 2014. © 2014 Wiley Periodicals, Inc.